2018
DOI: 10.1371/journal.pone.0197402
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant S100A16 expression might be an independent prognostic indicator of unfavorable survival in non-small cell lung adenocarcinoma

Abstract: S100A16 is a conserved member of the S100 protein family in mammals. Its upregulation was observed in many tumors and is related to malignant transformation. In this study, we explored the independent prognostic value of S100A16 in terms of overall survival (OS) and recurrence-free survival (RFS) by performing a retrospective study, using data in The Cancer Genome Atlas (TCGA)-lung adenocarcinoma (LUAD). Besides, by using deep sequencing data in TCGA-LUAD, we also explored the association between S100A16 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…DNA methylation represents the most common molecular mechanism of epigenetic modification when genes undergo changes such as cell proliferation or differentiation, alternative splicing, and genetic imprinting [ 43 45 ]. Studies have shown that DNA methylation can be closely related to the development of different tumors, thus making methylated genes potential biomarkers for the diagnosis and prognosis of lung cancer [ 24 , 46 48 ]. A previous study has indicated that the expression level of S100A16 might be modulated by its DNA hypomethylation and serves as an independent prognostic indicator of unfavorable OS and RFS in LUAD [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA methylation represents the most common molecular mechanism of epigenetic modification when genes undergo changes such as cell proliferation or differentiation, alternative splicing, and genetic imprinting [ 43 45 ]. Studies have shown that DNA methylation can be closely related to the development of different tumors, thus making methylated genes potential biomarkers for the diagnosis and prognosis of lung cancer [ 24 , 46 48 ]. A previous study has indicated that the expression level of S100A16 might be modulated by its DNA hypomethylation and serves as an independent prognostic indicator of unfavorable OS and RFS in LUAD [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that DNA methylation can be closely related to the development of different tumors, thus making methylated genes potential biomarkers for the diagnosis and prognosis of lung cancer [ 24 , 46 48 ]. A previous study has indicated that the expression level of S100A16 might be modulated by its DNA hypomethylation and serves as an independent prognostic indicator of unfavorable OS and RFS in LUAD [ 48 ]. There are studies of methylation levels in other genes that demonstrate the effect of methylation on the prognosis of LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Zhou et al have found that epithelial cell transforming 2 ( ECT2 ) expression is increased in LUAD and may predict poor OS and RFS for LUAD patients, but not for LUSC patients [31]. Using the UCSC Xena browser to analyze the same TCGA-LUAD dataset [32], Chen et al and Yu et al have demonstrated that high expression of lactate dehydrogenase-A ( LDHA ) [33] and the S100 protein family member S100A16 [34] might be independent prognostic markers of inferior OS for LUAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis was conducted as recommended in previous studies [2325]. In brief, GraphPad Prism 6.0 (GraphPad Inc., La Jolla, CA, USA) and SPSS 19.0 software package (SPSS Inc., Chicago, IL, USA) were used for data integration and analysis.…”
Section: Methodsmentioning
confidence: 99%